2019
DOI: 10.1016/j.eclinm.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes complications and comorbidity in Sub-Saharan Africans

Abstract: BackgroundContext-specific evidence of the spectrum of type 2 diabetes (T2D) burden is essential for setting priorities and designing interventions to reduce associated morbidity and mortality. However, there are currently limited data on the burden of T2D complications and comorbidity in sub-Saharan Africa (SSA).MethodsT2D complications and comorbidities were assessed in 2,784 participants with diabetes enrolled from tertiary health centres and contextualised in 3,209 individuals without diabetes in Nigeria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 44 publications
5
68
1
4
Order By: Relevance
“…8 The ocular complications of diabetes were found in 14-18% and signs of neuropathy were present in up to 48% of diabetics in sub-Saharan Africa. 9 Diabetic foot ulcers developed in 10-15% of people with diabetes at some stage of their lives and almost 50% of all DM-related admissions are due to diabetic foot problems in sub-Saharan Africa. 10 A previous study in Ethiopia identified that 29.4% of people with diabetes have experienced at least one chronic complication.…”
Section: Introductionmentioning
confidence: 99%
“…8 The ocular complications of diabetes were found in 14-18% and signs of neuropathy were present in up to 48% of diabetics in sub-Saharan Africa. 9 Diabetic foot ulcers developed in 10-15% of people with diabetes at some stage of their lives and almost 50% of all DM-related admissions are due to diabetic foot problems in sub-Saharan Africa. 10 A previous study in Ethiopia identified that 29.4% of people with diabetes have experienced at least one chronic complication.…”
Section: Introductionmentioning
confidence: 99%
“…2 The burden of diabetes-related complications and comorbidities are significant in Sub-Saharan Africans showing the urgent need for innovative public health approaches that prioritize the promotion of healthy lifestyles for prevention and early detection of T2DM. 21 Overall, a significant rise in the prevalence of diabetes is proved in almost all regions of the world in recent decades. The rise in the figure of individuals with diabetes or with a longer duration of diabetes is probable to change the disease profile in several populations around the world, mainly because of a greater incidence of diabetes-related complications like kidney failure and peripheral arterial disease.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of diabetes in Ethiopia in the adult population (20–79 years old) in 2019 was 3.2% [ 1 ]. Hypertension is the most common diabetes-related comorbidity in sub-Saharan Africa affecting significant proportion of patients with diabetes [ 3 , 4 ]. Optimization of glycemic control in patients with type 2 diabetes reduces the risk of developing diabetes comorbidities [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%